Effect of Aluminium closed-plate on energy absorption of hat-section tubes - Hashim, Hafizan; Hashim, Hanita; Hawa Mohd Yusoff, Siti; Affendi Jamal, Arif (International Journal of Engineering and Technology, 2018)
The hat-section tubes are a typical steel profile used in many structural applications. Among metals, steels are strong and excellently tough, but relatively heavy. The objective of this study is to investigate the possibility and generate design information on the uniaxial bending, impact, and energy absorption characteristics of hat-section tube with combination of lighter material. In this project, aluminium plate was used as a closed-plate to replace the relatively heavy mild steel plate. Finite element (FE) models were developed using ABAQUS and validated through experiment. Parametric studies were conducted mainly for investigating the dynamic impact response of the combined-material tubes. Present works were also compared with existing results of conventional tubes in order to demonstrate their workability. Results show that the use of alum closed-plate is a promising option for lighter hat-section tube while maintaining its strength and functionality. This was assured in comparison with conventional ones. In addition, wall thickness remains the most influential factor that affects crashworthiness characteristics of ductile materials in particular.Â